Intention to donate blood among students aged 17-22 years old - Ruengprateepseang, Nicharas; Poobrasert, Norapatra; Junprateep, Pakwan; Poungdang, Panissara; Sreeklin, Juthamas; Rattaphaet, Pattaraphorn; Muangsiri, Khaokwan; Mungkalarungsi, Sujimon (UBRU Journal for Public Health Research, 2023)
Currently, the blood shortage situation in Thailand is still a major problem that affects public health agencies or Thai Red Cross which are unable to supply enough blood to meet the increasing number of patients. Due to the shortage of blood donated, it is necessary to encourage donations and educate the public, especially the new generation of donors aged between 17 and 22 years old, who are an important force in alleviating the problem of a shortage of blood to donate in Thailand. To study blood donation-related knowledge, attitude toward blood donation and factors associated with the intention to donate blood. This study is a survey research, collecting data by google online form during 1 Mar -30 Apr 2023. The population in this study were students aged 17-22 years; 356 students participated in this study. Descriptive statistics such as frequency and percentage were used to analysis demographic data of the participants. Chi-Square was used to analyze factors associated with dependent variable. From a total of 356 participants, most were female (64.0%) and majority of participants were studying in grade 11-12 (36.80%). Most of them were interested to study in health science filed (36.8%). The household income of participants is mostly in range of 20,001-40,000 Bath per month (84.33%). Most participants had no experience donating their blood (69.4%), and either they or close relative had never received donated blood (79.49%). Regarding intention to donate blood, most participants answered “yes” (80.62%), followed by “not sure” (16.29%) and “no” (3.09%), respectively. Concerning blood donation-related knowledge, most participant had a moderate level of knowledge (71.06%), and the result showed a good level of attitude toward blood donation (58.42%). From analysing factors associated with intention to donate blood, it was found that class level (p=0.021) and having a blood donation experience (p=0.006) were associated with intention to donate blood in a statistically significant way. Participants had a moderate level of blood donation-related knowledge and most of them intend to donate blood, while majority of them had not never donate blood. Therefore, blood donation-related knowledge and attitude toward blood donation should be educated among students through their education institutions, in provinces, with consistency, as well as, knowledge regarding how to prepare themselves prior the donation such as resting, foods, and how to commute to donate blood in a specific area.